TYPOLOGY OF MAJLIS TA’LIM DISCOURSE; An Overview Towards Religious Discourse Constellation in Jember Regency - Hafidz Hafidz; Erfan Efendi (FALASIFA : Jurnal Studi Keislaman, 2022)
Majlis ta’lim is a necessity for the development of the reality of religious populism today. This type of religious group is a forum for the socio-political cultural structuring of today’s society. So that these religious groups have a role in constructing the social life of the community. In this context, the majlis ta’lim is deemed to have an interest in producing its discourse. Of course, everyone has understood that the religious discourse of religious assemblies (majlis) has a strong influence on the order of social life. The last fact was found that today’s religious assemblies (majlis) tend to contest, especially in the world of politics. On such problems, this research is important to do. The important issue that must be studied is how the awareness and religious views of the majlis ta’lim in seeing the various religious discourses that have existed so far that have been there? And how is the typology of discourse developed in response to it? Through a qualitative approach in the intentionality or Franz Brentano model of action qualitative approach, the research problem is trying to be studied. The result is an important picture of discourse production developed by this majlis. The conclusion is that the discourse production developed by this majlis has two different and contradictory typologies. The difference is the attitudes and religious values ​​developed in religious discourse.